Best Answer

I'm not sure this was notated correctly. As written, this is -11x plus or minus 18, which doesn't factor.

Q: What is the factor of 6x - 17x 18?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

The greatest common factor of 12xy2 + 6x is 6x. The greatest common factor of 12 and 6 is 6, and the greatest common factor of xy2 and x is x. If you took 6x out of both factors, the end result would be 2y2+1

x2 + 6x - 2 can not be factored

(6x + 5)(6x + 5) or (6x + 5)2

The GCF of 6x and 9x is 3x

Related questions

(x^18 - 6x^9 + 18)(x^18 + 6x^9 + 18)

6x² - 17x +12 = Quadratic equation X = (-b +/- (square root of b² - 4ac)) divided by 2a X = (--17 +/- square root of 289-288)) divided by 12 X = 1.5 or 1.333333 recurring

xx+3x+7=6x+18 xx+3x+7-(6x+18)=6x+18-(6x+18) xx-3x-11=0 Factors of -11: 1,-11 -1,11 Doesn't factor evenly, use quadratic

(x + 1)(x + 3)(x - 5)

The expression may be : 6x2 + 17x + 12 This factors as, 6x2 + 17x + 12 = (3x + 4)(2x + 3) Or, the expression could be : 6x2 - 17x + 12 This factors as, 6x2 - 17x + 12 = (3x - 4)(2x - 3)

(x + 3)(3x^2 - 4x + 6)

(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out

(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out

(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out

(3x-2)(2x+7) is the same as 6x^2 +17x -14 when the brackets are multiplied out

The given expression is: 4x² - 17x + 18 = 0 Determine the two integers such that the sum is -17 and the product is 4 * 18 = 72. They are -9 and -8. We can decompose -17x to: 4x² - 9x - 8x + 18 = 0 Factor-by-grouping, we obtain: x(4x - 9) - 2(4x - 9) = 0 Therefore, the factors are (4x - 9)(x - 2) If we want to determine the zeroes of the expression, set each binomial by 0 and solve for x. We obtain: 4x - 9 = 0 and x - 2 = 0 x = 9/4 and x = 2.

(9x - 10)(x + 3)